The attitude of the algerian muslim scholars association on the propositions of the algerian identity represented in the charters of the algerian national movement (1936-1954) - Chouayeb, Adel; Belhamel, Moufida (Journal of Human Sciences, 2023)
This article examines the different attitudes of the Association of Algerian Muslim Scholars on the propositions related to the issue of Algerian identity in the charters of the three cardinal national movements: the Charter of the Islamic Conference (1936), the Charter of February 10, 1943, and the Statement of November 1, 1954. The article investigates the Association’s contribution to the charters and the way it was influenced by them. Undoubtedly, the charters were mainly subject to the circumstances and the successive political and social developments of the period (1936-1954). Therefore, this article illustrates how the Association of Algerian Muslim Scholars shaped and materialized its concepts on the Algerian identity. The article, further, examines how the Association interacted with the three cardinal chapters based on its own concepts on national identity.